Cathepsin K osteoporosis trials, pycnodysostosis and mouse deficiency models: Commonalities and differences - DEMİRCİOĞLU, SERAP (TAYLOR & FRANCIS LTD, 2016)
Introduction: The osteoporosis market reached a value of more than $11 billion in 2015. Current treatments remain mostly antiresorptive and comprise of bisphosphonates, the anti-RANKL antibody, denusomab, and selective estrogen receptor modulators (SERMs). The most promising novel antiresorptives are cathepsin K inhibitors, which selectively target the bone matrix, degrading protease without interfering with osteoclast viability or formation as all other antiresorptives do.Areas covered: This review analyses the current status of cathepsin K inhibitor development, its side effects, and compares the phenotypes of mouse and human cathepsin K deficiencies with drug treatment outcomes.Expert opinion: Several selective cathepsin K inhibitors have been developed and evaluated in preclinical and clinical studies. Although all compounds were effective in reducing bone resorption markers, the development of some compounds was terminated either due to side effects or market competition. The most advanced compound is odanacatib, which significantly reduced bone fracture rates in a 5-year trial but still exhibits safety concerns. The analysis of mouse and human catK deficiencies sheds some light on the consequences of a cathepsin K inhibitor treatment. How predictive the knockout phenotypes are regarding long-term cathepsin K treatment remains unclear. Clearly, more studies are needed to understand the mechanism of the observed side effects and novel approaches are needed to make CatK inhibitors either osteoclast-specific or selective for the inhibition of the collagen matrix without affecting the other activities of the protease.
Keywords: Cathepsin K; cathepsin K knockout; odanacatib; osteoporosis; protease inhibitors; pycnodysostosis; BONE-MINERAL DENSITY; RESISTANT ACID-PHOSPHATASE; UPPER AIRWAY-OBSTRUCTION; POSTMENOPAUSAL OSTEOPOROSIS; CYSTEINE PROTEASE; COLLAGENOLYTIC ACTIVITY; INHIBITOR ODANACATIB; BIOCHEMICAL MARKERS; THERAPEUTIC TARGET; GROWTH-HORMONE